A question of procedural law: the principle of the inalterable nature of a tried case and the violation of EU law - Lopes, João Ramos (2014)
The reform operated in the regime of civil appeals by the Decree-law 303/2007, from 24 August 2007, introduced a new basis for an extraordinary appeal for review. This paper states our views on the (in)conformity with EU law of the solution put forward by the Portuguese legislator in order to ensure, on the one hand, the legal certainty and, on the other hand, the validity (here entailed in the jurisprudence of the CJEU), by establishing for the extraordinary appeal for review a maximum preclusion time limit of five years from the moment the ruling under review is passed, in cases in which the decision was made by a court of last resort, that failed to fulfill its obligation to ask for a preliminary ruling.